Hybrid spacecraft attitude control systems - Varatharajoo, Renuganth (2006)
The spacecraft missions are becoming more challenging in the recent years. Additionally, the requirements for space missions in terms of their performances are also gradually increasing. Therefore, the spacecraft have received attention for further optimisation. An approach would be to enhance the capabilities of each existing sub-system without altering the overall mass and volume budgets as in the same level today. Recent technology advances have triggered an appreciable enthusiasm towards off-the-shelf spacecraft subsystem concepts. The idea of combining the conventional Attitude Control System and the Electrical Power System is presented in this article. The Combined Energy and Attitude Control System (CEACS) consisting of a double counter rotating flywheel assembly is investigated for small satellites in this article. Another hybrid system incorporating the conventional Attitude Control System into the Thermal Control System (CATCS) is also investigated for small satellites herein. The CATCS consists of an electric conducting fluid that circulates in a closed loop (fluid wheel) simultaneously serving for the attitude and thermal controls. The governing equations describing both these novel hybrid subsystems are presented and their onboard architectures are numerically tested for their attitude performances. Both the investigated novel hybrid spacecraft subsystems comply with the reference mission requirements. Hence, the commissioning of these hybrid subsystems on the future spacecraft would benefit the mission, e.g. life duration, reliability and performance enhancements, mass and volume savings etc.